Предэпитаксиальная обработка подложек GaSb для жидкофазного выращивания гомоэпитаксиальных слоев - Andronova, О. V.; Kurak, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The results of investigation to find out the optimal conditions of pre-epitaxial GaSb substrate treatment by chemical etching in inorganic acid mixes are offered. It is shown that application of two-stage chemical treatment in HNO3:HF:H2O=3:1:2 and H2O2:HF:H2O=4:1:15 etchants give a possibility to satisfy the requirements for GaSb substrate in case of liquid phase epitaxy. Optimal conditions of pre-epitaxial GaSb substrate treatment provided the surface roughness value of no more than 0,05 mm and uniform substrate wetting by solution-melt are pointed out.